ELASTICITE EMPLOI DE LA CROISSANCE ECONOMIQUE ET SES DETERMINANTS MARCROECONOMIQUES AU CAMEROUN - Paul, Ningaye; Victor, Kitio; Arsene, Mba Fokwa (European Scientific Journal, ESJ, 2015)
The main objective of this paper is to determine the employment effects of growth in Cameroon. Specifically, it determines how employment responds at the global level and in each sector relative to change in production and indentifies variables likely to affect these changes. To this effect, we apply the employment elasticity method using macroeconomic determinants of employment elasticity on Cameroonian data. Our results globally suggest that economic growth affects positively employment. In effect, determining employment elasticity relative to GDP suggests that a 1% increase in economic growth will lead to a 0.41% increase in total employment. Sector-based elasticities show that agricultural employment is more sensitive to the value added of agricultural sector than to the GDP variations. Conversely, industrial employment is more sensitive to GDP variation than to the value added variation of this sector while employment in the services sector is sensitive to the GDP variation as to the value added variation of this sector. Moreover, the cost of employment, the share of the value added of the services sector in GDP as well as commercial opening affect positively the elasticity, at the same time, inflation and population growth rate rather affect it negatively. Based on these observations, the Cameroonian government should favor the development of industrial sector, the increase of employment productivity in the services sector, revalue employment cost, and stabilize inflation as well as the evolution of active population.